PENGARUH PELATIHAN DAN PENGEMBANGAN, MOTIVASI, KOMPETENSI TERHADAP KINERJA GURU SMA DI KOTA BATAM DI MEDIASI KOMITMEN ORGANISASI - Adi Neka Fatyandri; Teddi Firmawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
This study was conducted to examine the effect of Training and Development, Motivation, Competence on the Performance of High School Teachers in Batam City in the mediation of Organizational Commitment. The object of this research uses 3 schools in Batam City, namely SMAN 1 Batam, SMAN 3 Batam and SMAN 5 Batam, with a total population of 160 teachers. Determination of the sample using the Slovin Formula with a Margin Of Error 5% the result is 114 teachers obtained as a sample, data collection by distributing questionnaires through Google Forms in 3 schools and successfully filled out by 131 teachers. This research is quantitative, using Partial Least Square (PLS) for data processing, and the modeling technique used is Structural Equation Model (SEM). This study states that the Variables of Training and Development, Motivation, Competence have a significant positive effect on Organizational Commitment, Variables of Training and Development, Motivation, Competence and Organizational Commitment have a significant positive influence on Teacher Performance, Variables of Organizational Commitment Successfully Mediate the Variables of Training and Development, Motivation , Competence on Teacher Performance.